Trade Liberalization, Firm Performance, and Labor Market Outcomes in the Developing World : What Can We Learn from Micro-Level Data? - Epifani, Paolo (World Bank, Washington, DC, 2014)
reviews the micro-level evidence on the effects of trade and investment liberalization in the developing world. He focuses, in particular, on the effects of the 1991 trade reform in India since it provides an excellent controlled experiment in which the effects of a drastic trade regime change can be measured. His main findings are: 1) There is evidence of trade-induced productivity gains (in this respect, however, India is an exception. 2) These gains mainly stem from intra-industry reallocation of resources among firms with different productivity levels. 3) The gains are larger in import-competing sectors. 4) There is no evidence of significant scale efficiency gains. Unilateral trade liberalization is often associated with a reduced scale efficiency. 5) There is evidence of a pro-competitive effect of trade liberalization. 6) There is no evidence either of learning-by-exporting effects or of beneficial spillover effects from foreign-owned to local firms active in the same sectors. 7) There is evidence, however, of positive vertical spillovers from foreign direct investment. 8) There is evidence of skill upgrading induced either by technology imports or by trade-induced reallocations of market shares in favor of plants with higher skill-intensity. 9) There is no evidence of trade-induced increases in labor demand elasticities. But direct evidence suggests that trade exposure raises wage volatility. 10) There is no evidence of substantial employment contraction in import-competing sectors.